Validation of a computerised logMAR visual acuity measurement system (COMPlog): comparison with ETDRS and the electronic ETDRS testing algorithm in adults and amblyopic children - Laidlaw, D A H; Tailor, V; Shah, N; Atamian, S; Harcourt, C (British journal of ophthalmology, 2008)
Background/Aim:The COMPlog clinical visual acuity measuring system is being developed for both routine and research use. This study aimed to validate its performance in amblyopic children and both normal and diseased adults against the gold standard ETDRS chart and the E-ETDRS computerised acuity measurement algorithm.Method:Timed test and retest fully interpolated five letters per line logMAR visual acuity measurements were taken for 70 adults and 59 amblyopic children using the ETDRS chart and the COMPlog visual acuity measurement system. 39 of the adults also underwent computerised acuity testing using the E-ETDRS testing algorithm. The tested adults included normals as well as subjects with a range of ocular diseases. The methods of Bland and Altman were employed with test–retest variability (TRV) expressed as 95% confidence limits for agreement.Results:No significant bias was observed between the gold standard ETDRS acuity measurements and those taken with either COMPlog or E-ETDRS. TRVs of ±0.12 logMAR and ±0.10 logMAR were respectively found for COMPlog measurements in the amblyopic children and adult groups compared with ±0.12 logMAR for the ETDRS chart in both groups. The TRV of the E-ETDRS system was slightly greater at ±0.16 logMAR. Median testing times for COMPlog and ETDRS were 95 and 85 s and 66 and 56 s respectively in the paediatric and adult groups and 120 s for the E-ETDRS measurements on adults.Discussion:COMPlog measurements agree well with and are similarly reliable to the gold standard ETDRS chart with comparable test times. E-ETDRS algorithm measurements took approximately twice as long.